Ontario Retailers in the Early Twentieth Century: Dismantling the Social Bridge - Monod, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1993)
AbstractThis article explores the theory that late-nineteenth century and eary-twentieth century retailing served as an avenue to upward mobility. An examination of retailing in Ontario suggests two things: first, that shopkeeping was a deeply stratified occupation in which the poor remained marginalized at the bottom: and second, that over the course of the early twentieth century interest in retailing declined among working people as the business of storekeeping “professionalized”.